Subjectivity and institutional order - Hausner, Jerzy (Journal of Public Governance, 2014)
In the Cracow Circle, we have dealt with the links between self, cognition, and action. It seems to me that the issue of subjectivity is key for the understanding of interactions between these categories. Knowledge and action should not be divorced from the subject. There is no subject without knowledge. There is no subject without action. However, the relationships between the subject, knowledge and action are neither linear nor simple. There is no place for a cause-effect sequence or determinism. The author discusses subjectivity in the context of social relationships and interactions. From this point of view, subjectivity is a component of the social order and without subjectivity, or more accurately, without the existence of a number of social subjects, social order cannot emerge or last and evolve.